Implementasi “7 Poe Atikan” Bagi Karakter Siswa SMP di SMPN 1 Maniis - Mochammad Candra Agustian; Risman Suryana; Sidik Nurdiansyah; Jibal Nazib; Taofik Ahmad; Irsyad Irawan; Ai Nuryati; Faiz Karim Fatkhullah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Character education faces significant challenges due to digital disruption and globalization that trigger moral degradation in adolescents. In Purwakarta Regency, the "7 Poe Atikan" policy through Regent Regulation No. 69 of 2015 was implemented as a transformative solution based on local wisdom. This study aims to analyze the implementation mechanism, the character values ​​formed, and the supporting and inhibiting factors of the "7 Poe Atikan" program for students of SMPN 1 Maniis. This study uses a qualitative approach with a descriptive literature method. Data are sourced from official documents, educational reports, and related scientific articles over the past seven years. The analysis shows that the implementation of "7 Poe Atikan" in Maniis District effectively internalizes the values ​​of nationalism and love of culture through concrete practices such as the use of Basa Indung (mother language) and traditional clothing. However, significant challenges were found in the Betah di Imah aspect which indicates the still weak synergy between schools and parents. The implementation of "7 Poe Atikan" at SMPN 1 Maniis has successfully created an educational ecosystem that adapts to local wisdom, although strengthening collaboration with the family environment remains a priority for the sustainability of students' holistic character.